Effect of Baby Massage and Baby Gymnastics on Motoric Development of Infants Age 2-11 Months in the Darul Imarah Health Center Work Area Aceh Besar District - Intan Maisa Adilla; Yusnaini Yusnaini; Fithriany Fithriany; Cut Yuniwati; Kartinazahri Kartinazahri (Midwifery and Nursing Research, 2023)
Background : About 5 to 10% of children are thought to have developmental delays. Data on the incidence of general developmental delays are not known with certainty, but it is estimated that around 1-3% of children under the age of 5 experience general developmental delays. Based on data obtained from Aceh's health profile, in 2021 the number of live births will be 10 . 350 babies. Seeing the high number of live births in infants, it is very important to provide stimulus during the golden age so that developmental delays do not occur Method : This type of research is Quasy Experiment with two group pre-test and post-test design. The sample in this study were babies aged 2-11 months, a total of 34 people, of which 17 babies were given massage and baby gymnastic interventions while 17 babies were included in the control group. Results: The results of the study indicated that there were differences in the motor development of infants aged 2-11 months before and after massage and baby gymnastics with a p-value (0.000